2016
DOI: 10.1111/1365-2664.12667
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic ecology and the greening of cities

Abstract: 1.Ecologists are increasingly involved in city-making, especially in the development of green infrastructure and other designed plant communities. 2. Plant communities that are more phylogenetically related are more similar in functional traits and adaptations to their environment than distant relatives. 3. Knowledge of how evolutionary relationships among plant species influence ecosystem functions could be applied to green infrastructure to improve benefits such as urban cooling, habitat creation and stormwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 91 publications
1
19
0
Order By: Relevance
“…While MacIvor et al . () pointed out that the phylogenetic relationships of plant species should be considered when designing urban green infrastructures, our results show that we have to especially focus our efforts on protecting threatened native species and their habitats in order to safeguard phylogenetic diversity. For the flora of Halle (the same data set as used here) and by using a functional approach, we had identified the habitat conditions related to extirpation in a previous study (Knapp et al .…”
Section: Discussionmentioning
confidence: 89%
“…While MacIvor et al . () pointed out that the phylogenetic relationships of plant species should be considered when designing urban green infrastructures, our results show that we have to especially focus our efforts on protecting threatened native species and their habitats in order to safeguard phylogenetic diversity. For the flora of Halle (the same data set as used here) and by using a functional approach, we had identified the habitat conditions related to extirpation in a previous study (Knapp et al .…”
Section: Discussionmentioning
confidence: 89%
“…Functional traits provide a more mechanistic understanding of how species respond to environmental conditions (McGill, Enquist, Weiher, & Westoby, 2006) and can be more informative when monitoring impacts of land-use on biodiversity (Vandewalle et al, 2010;Williams et al, 2009). These measures of community composition can better identify species-specific differences and therefore improve GI design urban biodiversity (MacIvor, Cadotte, Livingstone, Lundholm, & Yasui, 2016).…”
Section: Gi Type and Taxa-specific Considerationsmentioning
confidence: 99%
“…An increasing number of studies aim to investigate the use of locally occurring native plant communities on green roofs (Butler et al, 2012;Heim & Lundholm, 2014;Simmons, 2015). Interpreting the phylogenetic community structure of species pools adapted to local microclimatic conditions that are similar to those experienced on green roofs, depending on spatial and temporal scale (Kraft, Cornwell, Webb, & Ackerly, 2007), could inform ecological design (Lundholm, 2006;MacIvor, Margolis, et al, 2016;MacIvor, Cadotte, et al, 2016). For example, a designed plant community could be based around one or a few key high-performing plant species, then other species added in order to maximize the community PD.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Phylogenetic diversity (hereafter referred to as PD) in plant communities has been considered in the implementation of ecological restoration (Hipp et al, 2015) and green infrastructure (MacIvor, Margolis, et al, 2016;MacIvor, Cadotte, Livingstone, Lundholm, & Yasui, 2016). However, very few studies have manipulated PD and demonstrated an impact on ecosystem services (Cadotte, 2013;Narwani, Matthews, Fox, & Venail, 2015).…”
mentioning
confidence: 99%